ANALYSIS OF THE USE OF ONLINE LEARNING APPLICATIONS DURING THE COVID-19 PANDEMIC IN BIOLOGY SUBJECTS - Aulia Sadila; Novi Fitriandika Sari (Jurnal Pelita Pendidikan, 2022)
The COVID-19 pandemic has had a negative impact on the life system in Indonesia, one of which is the education system. This study aims to analyze the use of online learning applications during the Covid-19 pandemic in biology subjects at SMAN 2 Rantau Utara. This research was quantitative research with a descriptive method. The sample of this research was the students of class XI MIA SMAN 2 Rantau Utara totaling 179 students who were taken by total sampling technique. The research instrument was in the form of a questionnaire on the use of online learning applications distributed through Google Forms and interview guidelines. Data analysis was carried out by calculating the percentage of scores obtained. The results showed that the online learning applications used by class XI MIA students of SMAN 2 Rantau Utara during the covid-19 pandemic were Google Meet at 57%, and Google Classroom at 43%. The indicators obtained for using online learning applications during the Covid-19 pandemic were: (1) Display of features/facilities in online learning applications used was 74%, (2) Interest in online learning applications used was 58.2%, (3) The provision of materials/tasks in the online learning applications used was 56.8%, (4) the independence of students towards online learning applications used in learning was 46.2%, and (5) the implementation of learning that occurred while using the online learning applications used by 42.6%. The use of online learning applications for biology subjects conducted online was a good solution to dealing with problems in the education system in the era of the covid-19 pandemic.